Knowing when someone is resilient: Development and validation of a measure of adaptive functioning among war-affected Sri Lankan Tamils - Alexandra O'Neill; Nuwan Jayawickreme; Laura E.R. Blackie; A. Demaske; Michelle A. Goonasekera; Eranda Jayawickreme (Elsevier, 2021)
Current measures of adaptive functioning are typically validated using samples from Western populations, which limit their utility in non-Western populations. The present study examines the development and utility of a locally derived measure of adaptive functioning, the Penn/RESIST/Peradeniya Competencies (PRPC) Scale, among Tamil survivors of the Sri Lankan civil war. This scale-developed using data from 622 qualitative interviews of war-affected Sri Lankan Tamils-was administered to three samples of war survivors (N ​= ​539) and was shown to have a three-factor structure that overlapped with domains identified through coding of the qualitative data: religious faith, community respect, and family responsibility. These three domains predicted lower levels of impaired functioning in daily life, as well as lower levels of depression and anxiety as measured by culturally sensitive assessments. Additionally, these domains predicted subjective trajectories of life satisfaction indicative of an adaptive sense of personal identity. These results highlight the value of culturally sensitive measures of adaptive functioning.